2022
DOI: 10.14417/ap.1900
|View full text |Cite
|
Sign up to set email alerts
|

Family foster care: Perceptions of Portuguese child protection professionals

Abstract: Family foster care (FFC) is the preferred out-of-home care measure for the protection of children and youth through Europe, in accordance with research findings of its superiority in meeting developmental needs of children and youth. Portugal, however, does not accompany the European trend in the implementation of FFC. Even after changes made to the law, prioritizing FFC, it represents only 2,7% of out-of-home placements (Instituto de Segurança Social, I.P. [ISS-IP], 2020).The main goal of this exploratory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Capacity building and provision of information on foster care arrangement to carers is a success factor in the childcare system. Negrao et al (2022) in a study to understand the perceptions of Portuguese child protection professionals regarding foster care, found that poorly defined training programs and monitoring processes were a stressing factor affecting the foster parenting experience and negatively impacting on the retention of foster families in the childcare system. Consequently, suitable training would provide adequate knowledge and skills that carers require in foster parenting services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Capacity building and provision of information on foster care arrangement to carers is a success factor in the childcare system. Negrao et al (2022) in a study to understand the perceptions of Portuguese child protection professionals regarding foster care, found that poorly defined training programs and monitoring processes were a stressing factor affecting the foster parenting experience and negatively impacting on the retention of foster families in the childcare system. Consequently, suitable training would provide adequate knowledge and skills that carers require in foster parenting services.…”
Section: Literature Reviewmentioning
confidence: 99%